Framing Detik.com dan Tempo.co Mengenai Proyek Ibu Kota Nusantara pada 100 Hari Kerja Prabowo-Gibran - Gustriatama, Qais Abhitah; Ahmad Zamzamy (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The research "Framing Online Media Coverage by Detik.com and Tempo.co on the Nusantara Capital Project during the First 100 Days of the Prabowo-Gibran Administration" aims to understand how Detik.com and Tempo.co frame news about the Nusantara Capital Project during the first 100 days of the Prabowo-Gibran administration, published from October 20, 2024, to January 28, 2025. This research is a qualitative descriptive study using Robert N. Entman's framing model, which has four analytical devices: defining the problem, determining the cause of the problem, making a moral judgment, and recommending a solution. The data sources come from three news articles published by Detik.com and three news articles published by Tempo.co. The research results show that the online media Detik.com and Tempo.co frame the sustainability of the Nusantara Capital City (IKN) development project from different perspectives. Detik.com emphasizes the sustainability of the IKN project as a priority for the Prabowo-Gibran administration. Tempo.co highlights the need for a reevaluation of the IKN project by the new administration.